The impact of age-related dysregulation of the angiotensin system on mitochondrial redox balance - Vajapey, Ramya; Rini, David; Walston, Jeremy; Abadir, Peter (Frontiers in Physiology, 2014)
Aging is associated with the accumulation of various deleterious changes in cells. According to the free radical and mitochondrial theory of aging, mitochondria initiate most of the deleterious changes in aging and govern life span. The failure of mitochondrial reduction-oxidation (redox) homeostasis and the formation of excessive free radicals are tightly linked to dysregulation in the Renin Angiotensin System (RAS). A main rate-controlling step in RAS is renin, an enzyme that hydrolyzes angiotensinogen to generate angiotensin I. Angiotensin I is further converted to Angiotensin II (Ang II) by angiotensin-converting enzyme (ACE). Ang II binds with equal affinity to two main angiotensin receptors—type 1 (AT1R) and type 2 (AT2R). The binding of Ang II to AT1R activates NADPH oxidase, which leads to increased generation of cytoplasmic reactive oxygen species (ROS). This Ang II-AT1R–NADPH-ROS signal triggers the opening of mitochondrial KATP channels and mitochondrial ROS production in a positive feedback loop. Furthermore, RAS has been implicated in the decrease of many of ROS scavenging enzymes, thereby leading to detrimental levels of free radicals in the cell.AT2R is less understood, but evidence supports an anti-oxidative and mitochondria-protective function for AT2R. The overlap between age related changes in RAS and mitochondria, and the consequences of this overlap on age-related diseases are quite complex. RAS dysregulation has been implicated in many pathological conditions due to its contribution to mitochondrial dysfunction. Decreased age-related, renal and cardiac mitochondrial dysfunction was seen in patients treated with angiotensin receptor blockers. The aim of this review is to: (a) report the most recent information elucidating the role of RAS in mitochondrial redox hemostasis and (b) discuss the effect of age-related activation of RAS on generation of free radicals.